If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4f + 7 = 9 Reorder the terms: 7 + 4f = 9 Solving 7 + 4f = 9 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 4f = 9 + -7 Combine like terms: 7 + -7 = 0 0 + 4f = 9 + -7 4f = 9 + -7 Combine like terms: 9 + -7 = 2 4f = 2 Divide each side by '4'. f = 0.5 Simplifying f = 0.5
| (3x+2)2+(4x-3)2=(5x-1)2 | | 6x^3+x^2+x=0 | | 6x^2+19x+7=-1 | | r-5.4=9.2 | | 9-n/3=28 | | 3x-5=4x+9 | | 100x^4+399x^2-4=0 | | 3(x+6)=3x+18 | | 11=2g-5 | | 876-4x=14x+19 | | 5-9x=190-44x | | -6w+18=20w | | 7=t-6-3 | | 3(m-3)+7(m+3)=16-4(7-m) | | 2x+3=4(x-1)+3 | | X^2-12x+36(x-6)=27(x-8) | | X+1+x=2+2x-1 | | 6k-3=-15 | | 7(x-4)-3=46 | | 2/5(25z-30)=3/5(12z+16) | | 12-8x=137-43x | | 81xy^3+3x^4=0 | | 122-3x=15x+20 | | 4(2x-8)-2=4(x-4)+6 | | 2x+28=9x-28 | | 3(4x-1)=48 | | 0.4(x-4)=7.2 | | 4xy^4-32xy=0 | | -9(x-4)-3=46 | | 0.5x-0.1(5-x)=2.2 | | 77/121 | | -7-6=7-8x |